2021
DOI: 10.1029/2021gb007069
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and Abiotic Controls on Dinitrogen Production in Coastal Sediments

Abstract: Nitrogen (N) is an essential nutrient that limits marine primary productivity and biogeochemical processes across a range of spatial and temporal scales (Canfield et al., 2010;Vitousek & Howarth, 1991). Historically, microbial N fixation has been the primary N source that converts dinitrogen gas (N 2 ) to biologically available forms, while denitrification has traditionally been recognized as the most important pathway through which fixed N is converted back to atmosphere (Devol, 2015). In response to 20 centu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…Soil anammox is a complex biochemical process that is conducted by anammox bacteria (Kartal et al, 2011; Zhu et al, 2019). Higher abundance of anammox bacteria generally induced a greater anammox rate (Sun et al, 2021). Gu et al (2017) showed that the anammox rates rose from 0.34 to 1.04 nmol N 2 g −1 h −1 as the abundance of anammox bacteria increased from 1.39 × 10 5 to 3.58 × 10 6 copies g −1 soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil anammox is a complex biochemical process that is conducted by anammox bacteria (Kartal et al, 2011; Zhu et al, 2019). Higher abundance of anammox bacteria generally induced a greater anammox rate (Sun et al, 2021). Gu et al (2017) showed that the anammox rates rose from 0.34 to 1.04 nmol N 2 g −1 h −1 as the abundance of anammox bacteria increased from 1.39 × 10 5 to 3.58 × 10 6 copies g −1 soil.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of anammox was enhanced by 129.4% with the concentrations of nitrite increasing by 107.7% (Meyer et al, 2005). Higher levels of ammonium can increase the abundance and activities of anammox bacteria, and ergo expedite the anammox rates (Bai, Xi, et al, 2015; Sun et al, 2021). The magnitude of anammox bacteria was grown from 4.86 × 10 6 to 6.11 × 10 6 copies g −1 soil, while the concentrations of ammonium increased from 10.0 to 20.5 mg kg −1 (Nie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%